Ice Jams in Alaska. Ice Engineering. Number 16, February 1997 - Eames, Heidi J.; White, Kate (1997)
An ice jam is an accumulation of ice in rivers that restricts flow and can cause destructive floods costly to riverine communities. Freezeup jams occur in early to midwinter when ice first forms in rivers. Breakup jams form in early spring when rising air temperature and/or rain events lead to rapid snowmelt, increases in runoff, and rapid increases in flow discharge. Ice covers break up and the resulting ice floes can become lodged at river bends, bridges, or narrow sections on the river or, more often, stop and accumulate where the river slope suddenly changes from relatively steep to mild. The ensuing blockage of the river cross section can cause a rapid rise in water levels that often leaves little time to prepare for flooding. Besides upstream flooding, ice jams often create serious problems to navigation. Damages to areas downstream of the ice jam can also be severe when the jam releases. The resulting water and ice surge can lead to the loss of barges and towboats, damages to mooring areas, bed and bank erosion, damage to wildlife and its habitat, and failure of bridges and other riverine structures. The original document contains color images.